Subgrain Rotation Recrystallization During Shearing: Insights From Full‐Field Numerical Simulations of Halite Polycrystals. Issue 11 (3rd November 2017) - Gomez‐Rivas, E.; Griera, A.; Llorens, M.‐G.; Bons, P. D.; Lebensohn, R. A.; Piazolo, S.
Abstract: We present, for the first time, results of full‐field numerical simulations of subgrain rotation recrystallization of halite polycrystals during simple shear deformation. The series of simulations show how microstructures are controlled by the competition between (i) grain size reduction by creep by dislocation glide and (ii) intracrystalline recovery encompassing subgrain coarsening by coalescence through rotation and alignment of the lattices of neighboring subgrains. A strong grain size reduction develops in models without intracrystalline recovery, as a result of the formation of high‐angle grain boundaries when local misorientations exceed 15°. The activation of subgrain coarsening associated with recovery decreases the stored strain energy and results in grains with low intracrystalline heterogeneities. However, this type of recrystallization does not significantly modify crystal preferred orientations. Lattice orientation and grain boundary maps reveal that this full‐field modeling approach is able to successfully reproduce the evolution of dry halite microstructures from laboratory deformation experiments, thus opening new opportunities in this field of research. We demonstrate how the mean subgrain boundary misorientations can be used to estimate the strain accommodated by dislocation glide using a universal scaling exponent of about 2/3, as predicted by theoretical models. In addition, this strain gauge can be potentially applied to estimate the intensity of intracrystalline recovery, associated with temperature, using quantitative crystallographic analyses in areas with strain gradients. Key Points: Full‐field numerical simulations of subgrain rotation recrystallization, able to reproduce experiments, are presented for the first time Intracrystalline recovery strongly decreases grain size reduction but does not change crystal preferred orientations Mean subgrain misorientations can be used as a strain gauge for polycrystals undergoing recrystallization, following a universal law